Prolegomeni di una profonda meraviglia sublime e come coltivarla oggi (Lebenswelt. Aesthetics and philosophy of experience., 2024)
In this work, I explored the complex relationship between psychological awe and the philosophical concept of the sublime. While psychology has often considered awe as a positive emotion distinct from the negative variant of the sublime, philosophical discourse has suggested an inherent historical and aesthetic connection between the two phenomena. I aimed to provide a preliminary contribution towards solving this puzzle, by relying on empirical findings from psychology and drawing from philosophical theories of Longinus, Kant, Schopenhauer and Hegel. I suggested a conceptualization of awe as a potential cultural evolution of the sublime, thus highlighting an overlap of key dimensions, such as vastness, self-transcendence, and alteration of sense of time. Moreover, I outlined practical insights and guidelines for eliciting awe in everyday life. Finally, the transformative nature of awe was explored by integrating psychological and philosophical perspectives, thus enabling a broader understanding of complex emotions and how they can influence human experience and wellbeing.